Unearthing the “Lost” Andean Root Crop “Mauka” (Mirabilis expansa [Ruíz & Pav.] Standl.). - Gendall, H. (2019)
Unearthing the “Lost” Andean Root Crop “Mauka” (Mirabilis expansa[Ruíz & Pav.] Standl.). Although recognized as part of the vibrant array of native roots and tubers that support farmers’ livelihoods in the Andean region, the root vegetable “mauka” (Mirabilis expansa (Ruíz & Pav.) Standl.) is little known outside the scattering of communities where it is cultivated and is considered at risk of disappearance. Based on fieldwork carried out in Peru in 2016, this study documents ethnobotanical knowledge of mauka through interviews with 40 farmers across the regions of Ancash, Huánuco, Puno, and Amazonas. Further, it re-evaluates the distribution of the crop and explores opportunities for conservation. Mauka was found to be more widely distributed in Peru than previously thought, and a total of 21 germplasm specimens were collected for ex situ conservation, including one landrace from Puno that had not been previously described. Farmers reported a substantial decline in mauka cultivation in their communities 20–50 years ago, with its lack of commercial value cited as a major reason for abandonment. Promisingly, through facilitating an encounter between several of these farmers and chefs at the renowned Peruvian restaurant Central, we demonstrate that revaluing mauka as a gastronomic ingredient could incentivize ongoing cultivation.